Juvencus' Four books of the Gospels Evangeliorum libri quattuor - Iuvencus, Gaius Vettius Aquilinus ca. 4. Jh (Routledge later Latin poetry, 2016)
"Juvencus' Evangeliorum libri quattuor or "Four Books of the Gospels," is a verse rendering of the gospel narrative written ca. 330 CE, an important text in literary and cultural history. This is the first English translation of the entire poem. The lack of a full English translation has kept many scholars and students, particularly those outside of Classics, and many educated general readers from discovering it. With a thorough introduction to aid in the interpretation and appreciation of the text this clear and accessible English translation will enable a clearer understanding of the importance of Juvencus' work to later Latin poetry and to the early Church." ...